2018
DOI: 10.1016/j.micromeso.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laplace NMR with hyperpolarized xenon gas

Abstract: Laplace NMR, consisting of diffusion and relaxation experiments, provides detailed information about dynamics of fluids in porous materials. Recently, we showed that two-dimensional Laplace NMR experiments can be carried out with a single scan based on spatial encoding. The method shortens the experiment time by one to three orders of magnitude, and therefore it is called ultrafast Laplace NMR. Furthermore, the singlescan approach facilitates significantly the use of nuclear spin hyperpolarization for boosting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The spatial encoding has been also exploited in 1D LNMR experiments, as well as in correlating T 1 relaxation or diffusion parameters with spectroscopic data . Recently, it has been applied also in two‐dimensional LNMR . This so‐called ultrafast LNMR method shortens the experiment time by one to three orders of magnitude as compared with corresponding conventional LNMR experiments.…”
Section: Ultrafast Laplace Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial encoding has been also exploited in 1D LNMR experiments, as well as in correlating T 1 relaxation or diffusion parameters with spectroscopic data . Recently, it has been applied also in two‐dimensional LNMR . This so‐called ultrafast LNMR method shortens the experiment time by one to three orders of magnitude as compared with corresponding conventional LNMR experiments.…”
Section: Ultrafast Laplace Nmrmentioning
confidence: 99%
“…On the other hand, the spatial encoding slightly lowers the sensitivity of the ultrafast LNMR experiment as compared with the conventional experiment . However, similarly to ultrafast NMR spectroscopy, ultrafast LNMR allows the use of nuclear spin hyperpolarization to increase the sensitivity of experiment, leading to the overall sensitivity enhancement of several orders of magnitude …”
Section: Ultrafast Laplace Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been used to develop ultrafast Laplace NMR experiments [17][18][19] which reduce the experiment time by one to four orders of magnitude compared to traditional approaches. 2 Consequently, ultrafast LNMR has been used to study molecular dynamics in a range of chemical systems including porous materials, 17,20 cellular metabolites, 21 and surfactant aggregates. 22 Nevertheless, these measurements can be limited by the low sensitivity of MR which is derived from perturbations of very small population differences across closely spaced nuclear spin energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that multidimensional LNMR data can be measured in a single scan using a high-field spectrometer. 40 42 Similar to ultrafast NMR spectroscopy 3 and to 1D diffusion 43 46 and relaxation experiments, 47 , 48 this so-called ultrafast LNMR method is based on spatial encoding of multidimensional data. We have previously shown that ultrafast LNMR is compatible with single-sided NMR, by exploiting the field gradient intrinsic to single-sided magnets for spatial encoding.…”
Section: Introductionmentioning
confidence: 99%